Pojęcie informacji publicznej i jej rodzaje - Jaśkowska, Małgorzata (Kwartalnik Prawa Publicznego, 2012)
The main aim of this article is to present the method of understanding public information in connection with the Act of 6 September 2001 on Access to Public Information, with consideration of the recent legislative changes. In reference books and jurisdiction two approaches emerged: a broad, subjective approach, referring to the constitution, and a narrow, objective one, based on Article 1 section 1 of the Act and the criterion of public matter. The author of this article, using pro-constitutional and community conforming interpretation of law, presents a number of arguments supporting the first understanding of this term. She emphasizes that legal aspects of the functioning of administration is insignificant from this perspective. It is not production of information by public entities that matters either, but the fact it was obtained and processed in order to perform their task. Thus, it cannot be applied only to official documents. At the same time, the author indicates an alarming tendency to limit the scope of public information by means of restricting forms of its availability, application of the so called internal documents concept or restricting access to the case record. In the subsequent section, various kinds of information classification were presented, heeding criteria of division and their consequences. The division into direct and processed information gains vital importance due to the dependence of providing processed information on the existence of particular public interest. In the above mentioned scope one may notice influence of recent amendments introduced to the Act on Access to Public Information. Although the amendment did not change the notion of information per se, it did introduce additional types of information. At the same time the amendment restricted access to public information and some types of direct information, in spite of Article 2a stipulating that the rules of reusing infringe neither the Act on Access to Public Information nor the freedom to spread it. The author’s belief is that comprehensive evaluation of the results of such a regulation will be largely dependent on administration and court practice with respect to these issues.